2021
DOI: 10.1111/jpc.15606
|View full text |Cite
|
Sign up to set email alerts
|

Progression from sepsis to septic shock and time to treatments in preterm infants with late‐onset sepsis

Abstract: Aim: Late-onset sepsis (LOS) in preterm infants can progress rapidly from minimal clinical signs and symptoms to septic shock which is associated with high mortality. The aim of this study was to describe the progression from sepsis to septic shock and evaluate our management performance with emphasis on time to treatments. Methods: This was a retrospective observational study including preterm infants ≤32 weeks gestation with LOS and septic shock defined as the requirement of fluids and vasopressors. Physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Various observational studies have assessed the haemodynamic response to LOS but few provided descriptive evidence of the haemodynamic presentation, clinical course of EOS and the progression to septic shock in this vulnerable age group 5–10,13–15 . Our clinical and ultrasound observational data revealed that preterm infants with EOS presented with either normal clinical findings and haemodynamic cardiac ultrasound parameters within the reference range, or with hypotension and higher as expected blood flows suggestive of warm shock.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Various observational studies have assessed the haemodynamic response to LOS but few provided descriptive evidence of the haemodynamic presentation, clinical course of EOS and the progression to septic shock in this vulnerable age group 5–10,13–15 . Our clinical and ultrasound observational data revealed that preterm infants with EOS presented with either normal clinical findings and haemodynamic cardiac ultrasound parameters within the reference range, or with hypotension and higher as expected blood flows suggestive of warm shock.…”
Section: Discussionmentioning
confidence: 74%
“…In our cohort, 59% of preterm infants with EOS progressed from sepsis to septic shock and this was associated with a significant increase in mortality. Considering the high mortality and the difficulty in diagnosing EOS clinically, one could argue that all preterm infants with risk factors for EOS should undergo routine assessment of vasodilatory changes, either with cardiac ultrasound or with alternative methods such as near‐red infrared spectroscopy 7,8,20 . A major advantage of an early cardiac ultrasound would be to identify signs of vasodilatory shock as soon as it develops.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations